The Radio Spectrum : Opportunities and Challenges for the Developing World - Wellenius, Björn; Neto, Isabel (World Bank, Washington, DC, 2012)
The radio spectrum is a major component of the telecommunications infrastructure that underpins the information society. Spectrum management, however, has not kept up with major changes in technology, business practice, and economic policy during the past two decades. Traditional spectrum management practice is predicated on the spectrum being a limited resource that must be apportioned among uses and users by government administration. For many years this model worked well, but more recently the spectrum has come under pressure from rapid demand growth for wireless services and changing patterns of use. This has led to growing technical and economic inefficiencies, as well as obstacles to technological innovation. Two alternative approaches are being tried, one driven by the market (spectrum property rights) and another driven by technology innovation (commons). Practical solutions are evolving that combine some features of both. Wholesale replacement of current practice is unlikely, but the balance between administration, property rights, and commons is clearly shifting. Although the debate on spectrum management reform is mainly taking place in high-income countries, it is deeply relevant to developing countries as well.